Nanoscratch testing for the assessment of enamel demineralization under conditions simulating wine erosion. (March 2015) - Kwek, SXR; Mian, M; Hall, C; Xie, Z; Yong, R; Kaidonis, J; Townsend, GC; Ranjitkar, S
Abstract Background Erosive tooth wear and dentinal hypersensitivity are common problems affecting professional wine tasters. By using nanoscratch testing, the aim of this in vitro study was to assess enamel softening under conditions simulating 10 one‐minute episodes of wine erosion. Methods Ten enamel specimens were bathed in artificial saliva for 2 hours before being eroded for 10 episodes, with each episode comprising one minute of wine erosion followed by one minute of remineralization in artificial saliva. Nanoscratches were placed with a spherical tip (20 μm radius) in a nanoindenter under a load of 100 mN at baseline (stage 1), after a one‐erosion episode (stage 2) and after 10‐erosion episodes (stage 3). Results There were significant effects of erosion stages on both scratch depth (p < 0.001) and surface roughness (p < 0.001). Post hoc tests showed significant differences in both scratch depths and surface roughness between stages 1 and 3 (p < 0.001), and between stages 2 and 3 (p < 0.01). Conclusions Enamel softening occurs at an early stage of wine tasting, emphasizing the need to implement early preventive strategies in professional wine tasters. Further research elucidating the fundamental mechanisms involved in early stages of erosion has the potential to lead to development of more effective preventive strategies.